Desired attachment and breakup distress relate to automatic approach of the ex-partner. (June 2022) - Eisma, Maarten C.; Tõnus, Dan; de Jong, Peter J.
Abstract: Background and objectives: Romantic relationship breakups can lead to severe emotional disturbances including major depression. Anxious attachment and desired attachment with the ex-partner are hypothesized to elicit repetitive thought about the breakup and the former partner and attempts to reunite with (i.e. approach) the ex-partner, which fuel breakup distress. Since prior research on this topic has mostly used survey methodology, the study aim was to examine the relations between above-mentioned variables employing a behavioral measure of approach of the ex-partner. Methods: Automatic approach-avoidance tendencies toward the former partner were assessed with an Approach Avoidance Task (AAT). Sixty-two students (76% female) moved a manikin towards or away from stimuli pictures (ex-partner, matched stranger, landscape) as fast as possible based on the stimulus frame color (blue, yellow). Participants also completed questionnaires assessing anxious attachment, desired attachment, repetitive thought about the breakup (rumination) and the ex-partner (yearning), and breakup distress (prolonged grief symptoms). Results: Anxious attachment related positively to rumination and breakup distress. Desired attachment related positively to yearning, automatic approach bias toward the ex-partner, and breakup distress. Both anxious and desired attachment, rumination, yearning, and approach bias related positively to breakup distress. Limitations: The use of a student sample may limit generalizability. A correlational design precludes causal conclusions. Conclusions: Together with prior work, results suggests anxious attachment hampers psychological adaptation to a breakup by increasing the use of ruminative coping. Desire to retain an attachment bond with the ex-partner, expressed in yearning and approach of the ex-partner, may also worsen breakup distress. Highlights: Attachment and attempts to reunite with the ex-partner may worsen breakup distress. We used a novel Approach Avoidance Task to assess automatic approach of an ex-partner. Attachment anxiety related positively to rumination and breakup distress. Desired attachment related positively to yearning and breakup distress. Desired attachment and breakup distress related positively to automatic approach bias.